2021
DOI: 10.15585/mmwr.mm7023e2
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in COVID-19 Cases, Emergency Department Visits, Hospital Admissions, and Deaths Among Older Adults Following the Introduction of COVID-19 Vaccine — United States, September 6, 2020–May 1, 2021

Abstract: vaccine administration data are reported to CDC by multiple entities using immunization information systems, the Vaccine Administration Management System, pharmacy systems, or direct submission of electronic health records. (https:// www.cdc.gov/coronavirus/2019-ncov/vaccines/distributing/about-vaccine-data. html). Persons were considered fully vaccinated if they received the second dose in a 2-dose COVID-19 vaccine series (Pfizer-BioNTech or Moderna) or 1 dose of the single-dose Janssen (Johnson and Johnson) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
68
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 7 publications
4
68
2
5
Order By: Relevance
“…Previous studies have shown that, by May 2021, more than 40,000 deaths had been prevented due to vaccination of the elderly population in Brazil with the Oxford-AstraZeneca and CoronaVac-Sinovac/Butantan vaccines [ 7 ]. Similar findings were found in the US after use of the first dose of Pfizer-BioNTech, particularly in older adults [ 9 ]. A study in Tennessee/USA showed a reduction of more than 95% in mortality in the vaccinated elderly population between December 2020 and March 2021 [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that, by May 2021, more than 40,000 deaths had been prevented due to vaccination of the elderly population in Brazil with the Oxford-AstraZeneca and CoronaVac-Sinovac/Butantan vaccines [ 7 ]. Similar findings were found in the US after use of the first dose of Pfizer-BioNTech, particularly in older adults [ 9 ]. A study in Tennessee/USA showed a reduction of more than 95% in mortality in the vaccinated elderly population between December 2020 and March 2021 [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…The widespread availability and administration of COVID-19 vaccines has changed the trajectory of the pandemic in the United States and significantly reduced hospitalization and mortality among vaccinated persons ( 1 ). Increasing the proportion of eligible persons who are vaccinated reduces the risk for substantial or high community-wide transmission, which in turn reduces the risk for the emergence of new variants that could have the potential to overcome vaccine-induced immunity.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccination remains the most effective means to achieve control of the pandemic. In the United States, COVID-19 cases and deaths have markedly declined since their peak in early January 2021, due in part to increased vaccination coverage ( 1 ). However, during June 19–July 23, 2021, COVID-19 cases increased approximately 300% nationally, followed by increases in hospitalizations and deaths, driven by the highly transmissible B.1.617.2 (Delta) variant * of SARS-CoV-2, the virus that causes COVID-19.…”
mentioning
confidence: 99%
“…Figure 1 highlights the 7-day average cumulative cases of COVID-19 in five countries: the United States, Canada, Germany, the Netherlands, and Nigeria. Recently, when the distribution of COVID-19 vaccination became more accessible in most communities in the United States, the daily hospitalization cases due to infection and related death decreased significantly [6][7][8][9]. However, overwhelming evidence indicates differences in infection and associated death rates across different populations [2,3].…”
Section: Introductionmentioning
confidence: 99%